Modal Dynamics of Large Wind Turbines with Different Support Structures - Bir, G.; Jonkman, J. (National Renewable Energy Laboratory (U.S.), 2008)
This paper presents modal dynamics of floating-platform-supported and monopile-supported offshore wind turbines.